2019
DOI: 10.3847/1538-4357/ab3121
|View full text |Cite
|
Sign up to set email alerts
|

Two Types of Confined Solar Flares

Abstract: With the aim of understanding the physical mechanisms of confined flares, we selected 18 confined flares during 2011-2017, and classified the confined flares into two types based on their different dynamic properties and magnetic configurations. "Type I" of confined flares are characterized by slipping reconnection, strong shear, and stable filament. "Type II" flares have nearly no slipping reconnection, and have a configuration in potential state after the flare. Filament erupts but is confined by strong stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 105 publications
2
21
1
Order By: Relevance
“…5. By analyzing the dynamic evolution of 26 confined flares occurring in ARs with Φ AR ≥1.0×10 23 Mx, we find that these flares have several characteristics in common: stable filament, slipping magnetic reconnection and strongly sheared PFLs, belonging to "type I" flares as proposed in our previous work (Li et al 2019).…”
Section: Summary and Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…5. By analyzing the dynamic evolution of 26 confined flares occurring in ARs with Φ AR ≥1.0×10 23 Mx, we find that these flares have several characteristics in common: stable filament, slipping magnetic reconnection and strongly sheared PFLs, belonging to "type I" flares as proposed in our previous work (Li et al 2019).…”
Section: Summary and Discussionmentioning
confidence: 61%
“…The confined flares from ARs with Φ AR ≥1.0×10 23 Mx are characterized by slipping reconnection, strong shear, and a stable filament. They belong to "type I" confined flares proposed by Li et al (2019), who classified confined flares into two types based on their different dynamic properties and magnetic configurations. Similar to the appearance of confined flares in AR 12192 (Li et al 2019), the filaments in ARs 11339, 11520 (Figures 6-7), 11967 and 12242 (Figures 8-9) were all stably present and seemed not to be involved in the flare evolution.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If a flux rope in an active region remains stable (or is even entirely absent), reconnection between sheared magnetic fields can still lead to flares without a CME (Li et al 2019), a scenario that has been proposed to explain the observed behaviour of NOAA active region 12192 (Jiang et al 2016). This scenario may serve as another resolution to the missing stellar CME conundrum, but it remains to be seen how frequently such flares actually occur.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The characteristics of eruptive flares have been well described by the standard flare model. The characteristics of confined flares are studied by comparison of the physical parameters between the eruptive and confined flares (Falconer et al 2006;Kliem & Török 2006;Cheng et al 2011;Harra et al 2016;Zhang et al 2017;Li et al 2019). Those studies suggest that the magnetic configuration, such as overlying field strength, decay index, and non-potentiality of an active region core, could be a determining factor of a confined flare.…”
Section: Introductionmentioning
confidence: 99%